Pannexin 1 as a driver of inflammation and ischemia–reperfusion injury - Koval, Michael (Purinergic Signal, 2021)
Pannexin 1 (Panx1) is a ubiquitously expressed protein forming large conductance channels that are central to many distinct inflammation and injury responses. There is accumulating evidence showing ATP released from Panx1 channels, as well as metabolites, provide effective paracrine and autocrine signaling molecules that regulate different elements of the injury response. As channels with a broad range of permselectivity, Panx1 channels mediate the secretion and uptake of multiple solutes, ranging from calcium to bacterial derived molecules. In this review, we describe how Panx1 functions in response to different pro-inflammatory stimuli, focusing mainly on signaling coordinated by the vasculature. How Panx1 mediates ATP release by injured cells is also discussed. The ability of Panx1 to serve as a central component of many diverse physiologic responses has proven to be critically dependent on the context of expression, post-translational modification, interacting partners, and the mode of stimulation.